INSTAGRAM SEBAGAI MEDIA PUBLIKASI DALAM MEMBANGUN BRAND AWARENESS JAKARTA AQUARIUM - Shintadevy Maryolein; Nadya Dwina Hapsari; Rani Chandra Oktaviani (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2019)
Jakarta Aquarium is an ex-situ conservation and education institution located in Neo Soho Mall, West Jakarta. As a newly established institution, Jakarta Aquarium wants its brand to be used by the wider community. The efforts made by the Public Relations Jakarta Aquarium are to utilize the features available on Instagram. The purpose of this research was to find out strengths and weaknesses the utilization of Instagram as a media publication for Jakarta Aquarium to build brand awareness. The theory used in this study is new media theory and supported by Public Relations concepts, publication concepts, and Instagram. This study uses a qualitative descriptive method that designed by data collection techniques in the form of structured interviews, literature studies and internet reviews, especially on Instagram Jakarta Aquarium activities. The findings obtained in this study are the use of Instagram has maximized Instagram’s role as a platform to media publicity, consistent in managing the feed display and upload interesting content so that it can build Jakarta Aquarium's brand awareness in the wider community. In addition, through this research the researcher can find out more about the advantages of the Jakarta Aquarium’s Instagram that has made it easier for people to access all information quickly and easily, and establish two-way communication with their followers. Also, the disadvantages of Jakarta Aquarium’s Instagram that still uploads more promotional content than the educational content on Instagram.